The History of the Position of Yasovulboshi in the Khiva Khanate (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2025)
This article discusses the form of governance in the Khiva Khanate and elaborates on the rights, powers, and duties of the position of yasovulboshi (chief enforcer or marshal). It seeks to shed light on issues related to the influence of this position on state administration.